NILAI PENDIDIKAN KARAKTER DALAM NOVEL DI TANAH LADA KARYA ZIGGY ZEZSYAZEOVIENNAZABRIZKIE - Wahyudi Syahrir; Sakaria Sakaria (Universitas Negeri Makassar, 2022)
The Value of Character Education in Novels in Tanah Lada by ZiggyZezsyazeoviennazabrizkie. This study aims to describe (1) the values of character educationand (2) the form of conveying the values of character education in the novel Tanah Lada byZiggy Zezsyazeoviennazabrizkie. This research is a qualitative descriptive study that analyzesthe values of character education and the form of delivery of character education values in thenovel in Tanah Lada by Ziggy Zezsyazeoviennazabrizkie. The results show that all the mainvalues of character education based on the Minister of Education and Culture Number 18 of2015 are contained in the novel in Tanah Lada by Ziggy Zezsyazeoviennazabrizkie and theform of direct delivery of the value of character education in the novel in Tanah Lada usesmodalities (must, should) and claim clauses ( that means, it means) so that the moral messageto be conveyed can be directly identified. Meanwhile, to form this indirectly, you can enjoythe sentences contained in the novel.